Culture and political marketing: the case of female candidates in 2014 Parliamentary election in the Kingdom of Bahrain - Abdul Wahab, Al Jawder; Mokhtar, KhairiahSalwa (School of Social Sciences, USM, 2017)
This study investigates the female candidates’ practices during the parliamentary election to explore their strategies in political marketing in 2014. Parliamentary election is at an infancy stage in the country. The area of the Arabian Gulf States is new to democracy and parliament election. Its culture is described as Arab-Muslim and tribalism that has its impact on the female candidates to the extent that they can be characterized as relationship-oriented candidates. The study applied Grounded Theory the appropriate strategy in data collection and analysis. Interviews were held with ten female candidates. Two daily newspapers (Akhbar Al Khaleej and Al Ayam), and social media (Instagram and Twitter), posters and advertisements were secondary sources. Data were collected in the period between 1st October and 31st December 2014. It would be better if the research covered earlier period. The findings show that the female candidates practices relationship-oriented approach of political marketing and were controlled by culture in their election campaigns. Furthermore, the female candidates relied on relationships with stakeholders to stand for election. The study contributes to the field of political marketing. The study provides more understanding of the Arab-Muslim culture which influences the parliamentary candidates in election in general and female candidates in specific.